Factors of adoption shariah governance in the halal hospitality and tourism industry / Zulaipa Ruzulan ... [et al.] - Ruzulan, Zulaipa; Jamaludin, Mohammad Aizat; Hassan, Rusni; Has-Yun Hashim, Khairusy Syakirin; Fathullah Harun, Hanifah Musa (Universiti Teknologi MARA, 2024)
The halal industry has been globally recognized as an essential niche segment in many established industries in Malaysia, including hospitality and tourism. This is due to the industry’s potential to attract both Muslim and non-Muslim travellers to access products and services that meet Shariah requirements. Therefore, robust Shariah governance is needed for the industry players to monitor the activities accordingly. However, to what extent is the commitment of the tourism stakeholders, especially from the authoritative policymakers, to ensure that effective monitoring can be achieved, given the limited research in this area of governance? This paper will investigate the factors that lead to the establishment of Shariah governance in the halal hospitality and tourism industry. A qualitative research methodology is used in this study, employing an in-text document analysis technique to obtain data, supported by content analysis to analyse the data simultaneously. The research has found that the state authorities play a significant role in realising the mission to implement an ideal Shariah governance with strong support from the federal government. It is hoped that this study will contribute to policymakers and hospitality and tourism players committing to governance practices aligned with the Shariah principle when offering and promoting the products and services in the halal hospitality and tourism industry.